Mitochondria Practical Protocols - Leister, Dario; Herrmann, Johannes M.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2007)
Mitochondria: Practical Protocols offers a broad collection of methods for studying the molecular biology, function, and features of mitochondria. In the past decade, mitochondrial research has elucidated the important influence of mitochondrial processes on integral cell processes such as apoptosis and cellular aging. This practical guide presents a wide spectrum of mitochondrial methods, each written by specialists with solid experience and intended for implementation by novice and expert researchers alike. Part I introduces major experimental model systems and discusses their specific advantages and limitations for functional analysis of mitochondria. The concise overview of general properties of mitochondrial systems is supplemented by detailed protocols for cultivation of model organisms. Parts II-VI comprise a robust collection of protocols for studying different molecular aspects of mitochondrial functions including: genetics and microbiology, biochemistry, physiology, dynamics and morphology, and functional genomics. Emphasis is placed on new and emerging topics in mitochondrial study, such as the examination of apoptotic effects, fusion and fission of mitochondria, and proteome and transcriptome analysis.
Model Systems to Study Mitochondrial Functions -- The Mitochondria of Cultured Mammalian Cells -- The Mitochondria of Cultured Mammalian Cells -- Drosophila melanogaster as a Model System to Study Mitochondrial Biology -- Isolation and Functional Analysis of Mitochondria From the Nematode Caenorhabditis elegans -- Isolation of Mitochondria From Procyclic Trypanosoma brucei -- Saccharomyces cerevisiae as a Model Organism to Study Mitochondrial Biology -- Studying Mitochondria in an Attractive Model: Schizosaccharomyces pombe -- Neurospora crassa as a Model Organism for Mitochondrial Biogenesis -- Isolation of Intact, Functional Mitochondria From the Model Plant Arabidopsis thaliana -- Chlamydomonas reinhardtii: The Model of Choice to Study Mitochondria From Unicellular Photosynthetic Organisms -- Genetics and Molecular Biology -- Directed Alteration of Saccharomyces cerevisiae Mitochondrial DNA by Biolistic Transformation and Homologous Recombination -- Screens for Mitochondrial Mutants in Yeast -- Transcript End Mapping and Analysis of RNA Editing in Plant Mitochondria -- In Vitro Analysis of the Yeast Mitochondrial RNA Polymerase -- Functional Analysis by Inducible RNA Interference in Drosophila melanogaster -- Analysis of Replicating Mitochondrial DNA by Two-Dimensional Agarose Gel Electrophoresis -- Biochemistry -- The Analysis of tRNA Import Into Mammalian Mitochondria -- Analysis of Mitochondrial Protein Synthesis in Yeast -- Large-Scale Isolation of Mitochondrial Ribosomes From Mammalian Tissues -- Protein Import Into Isolated Mitochondria -- Analyzing Import Intermediates of Mitochondrial Proteins by Blue Native Gel Electrophoresis -- In Vitro and In Vivo Protein Import Into Plant Mitochondria -- Two-Dimensional Blue Native/Blue Native Polyacrylamide Gel Electrophoresis for the Characterization of Mitochondrial Protein Complexes and Supercomplexes -- Investigation of Iron-Sulfur Protein Maturation in Eukaryotes -- Studying Proteolysis Within Mitochondria -- Physiology -- Methods to Determine the Status of Mitochondrial ATP Synthase Assembly -- ATP Production in Isolated Mitochondria of Procyclic Trypanosoma brucei -- Oxidative Stress and Plant Mitochondria -- Measuring Mitochondrial Shape Changes and Their Consequences on Mitochondrial Involvement During Apoptosis -- Assessing Mitochondrial Potential, Calcium, and Redox State in Isolated Mammalian Cells Using Confocal Microscopy -- Dynamics and Morphology -- Fluorescence Imaging of Mitochondria in Yeast -- Mitochondrial Fusion In Vitro -- Conventional and Immunoelectron Microscopy of Mitochondria -- Mitochondrial Division in Caenorhabditis elegans -- Functional Genomics -- Yeast Mitochondrial Transcriptomics -- Plant Mitochondrial Transcriptomics by Quantitative RT-PCR -- Proteomics of Yeast Mitochondria -- Arabidopsis Mitochondrial Proteomics -- MitoP2, an Integrated Database for Mitochondrial Proteins.
Keywords: Life sciences; Human genetics; Cell biology; Life Sciences; Cell Biology; Human Genetics; Electronic books